The face mask as art: contemporary artistic expressions of diseases and COVID-19 - Sequeira-Rovira, Paula (2022)
This article is interested in the expressions of art linked to the disease. Although historically these representations have shown closeness to ugliness or the unpleasantness of the pathological, in pandemic times, other symbolisms have been produced. In the case of the surgical mask, it has been used not only as a metaphor to show its closeness to the pandemic caused by SARS-CoV-2, but also to express individualistic ideas of how to handle the pandemic and a more personal management of the health crisis. Special importance has been given to the exhibitions of “Masks x artists”, organized by the Jade Museum in Costa Rica, and “Mask of art. My only protection” from Puerto Rico. Likewise, other types of artistic spaces that are interested in COVID-19, where this device has a prioritary position, were mentioned in this study.